BUDGET RATCHETING IN GOVERNMENTAL BUDGETING: AN EMPIRICAL INVESTIGATION - Misra, Fauzan (Badan Pemeriksa Keuangan Republik Indonesia, 2020)
Previous literature has documented various aspects of behavior in the budgeting process. Behavioral problems that are often discussed include budgetary slack and opportunistic behavior that occur due to information asymmetry. However, there is little attention to behavioral problems in previous studies called ratcheting behavior. This study investigates such behavior in a governmental budgeting setting. Besides, this study extends by testing ratchet behavior when local government adopts a well-known budget control mechanism, called analysis on standardized expenditure. To accomplish this purpose, study participants role-played as the budget preparer on a government budgeting task. The experiment used a web-based instrument that involved 51 participants. Results showed that budget preparer engaged in a ratchet behavior when setting their budget. Furthermore, budget ratcheting did not occur when preparer using an analysis of standardized expenditure. However, this situation only remains for one year. In the next year, preparer engaged in a ratchet behavior, at a lower intention. These findings underscore the importance of analysis of standardized expenditure in a government budgeting process environment. As a practical contribution, these findings suggest that using and monitoring for the adoption of analysis on standardized expenditure should be maintained continuously.